A new checklist of Slovenian leeches (Hirudinea: Euhirudinea): In memory of Boris Sket (1936–2023) - Peter Trontelj; Patricija Podkrajšek (Natura Sloveniae)
The new (as of 2023) checklist of Slovenian leeches (Euhirudinea) contains 33 species, which represents a 44% increase since the last published inventory in 2003. Notable new entries include Placobdella costata found parasitizing on European pond turtles, the marine fish leech Trachelobdella lubrica from the Slovenian Adriatic coast, the semi-terrestrial Haemopis elegans, the terrestrial Xerobdella praealpina – making Slovenia possibly the only country with confirmed occurrence of all three European land leeches – and a new, still undescribed highly troglomorphic cave leech from a deep Dinaric cave. The number of freshwater fish leeches is underwhelmingly low: two. This, and several unresolved taxonomic questions in erpobdellids suggest that more faunistic and taxonomic work is needed and that the list of Slovenian leech species is far from concluded. The authors dedicate this contribution to their teacher, Prof. Boris Sket (1936–2023), a leading figure in biodiversity research in the Dinaric Karst, including leeches and cave life.